2019
DOI: 10.1371/journal.pone.0198919
|View full text |Cite
|
Sign up to set email alerts
|

Improving preterm newborn identification in low-resource settings with machine learning

Abstract: Background Globally, preterm birth is the leading cause of neonatal death with estimated prevalence and associated mortality highest in low- and middle-income countries (LMICs). Accurate identification of preterm infants is important at the individual level for appropriate clinical intervention as well as at the population level for informed policy decisions and resource allocation. As early prenatal ultrasound is commonly not available in these settings, gestational age (GA) is often estimated us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Signal processing and machine learning have also been used to estimate perinatal risk factors-eg, to automatically estimate gestational age using data from ultrasound images and other patient variables. [47][48][49] Studies reported high accuracy (>85%) relative to trained experts and other standard gestational age estimation techniques.…”
Section: Diagnosismentioning
confidence: 99%
“…Signal processing and machine learning have also been used to estimate perinatal risk factors-eg, to automatically estimate gestational age using data from ultrasound images and other patient variables. [47][48][49] Studies reported high accuracy (>85%) relative to trained experts and other standard gestational age estimation techniques.…”
Section: Diagnosismentioning
confidence: 99%
“…Prenatal diagnosis of fetal abnormalities has greatly benefited from advances in US technology and, in the last years, also from the advances in ML. ML algorithms have been used in different applications within fetal US medicine such as to predict preterm births [43,44], the risk of euploidy, trisomy 21, and other chromosomal aneuploidies [45] or prediction of perinatal outcomes on asymptomatic short cervical length [46] among others. Regarding fetal cardiology, one of the subfields in which ML has been extensively applied in the last decades is improvement of the diagnosis of fetal hypoxia or acidemia based on the analysis of CTG.…”
Section: For Fetal Diagnosismentioning
confidence: 99%
“…Few studies elaborating ML-tools for prediction of survival of preterm neonates are currently available; see, for example, [11] describing ML-models for estimation of mortality risk of very preterm neonates. Recent works [12] elaborated ML-models for more precise assessment of gestational age and to improve identification of preterm neonates.…”
Section: Introductionmentioning
confidence: 99%